Effects of hypoxia on the serotonin (Revista Española de Fisiología, 1967)
The hypoxia produces alterations of the corporal valuation of serotonin specially at level of the pulmonary and the intestinal tissue. In the first case a significant increase is observed in likely relation with the hypertensive hypoxia mechanism. The intestinal decrease might be the consequence of the deficient trofism of the mucosa. During the hypoxia there is a disminution of the excretion of serotonin namely, the wole metabolism disminishes.